Gender, perception of audits, access to finance, and self-assessed corporate tax compliance - Sunardi Sunardi; Theresia Woro Damayanti; Supramono Supramono; Yustinus Budi Hermanto (Economies, 2022)
This study explores the influence of financial statement audits on tax compliance directly and indirectly through access to finance, and it examines gender roles to improve tax compliance through access to finance and financial statement audits. The sample for this study consisted of 45,504 businesses located in developing countries, as determined by The World Bank Enterprise Survey 2006-2018. The primary findings of this study demonstrate that the audit of financial statements has a positive impact on tax compliance through access to finance. Another result is that firms with female top managers are more likely to comply with their tax obligations than those with male top managers. The key to improving tax compliance is that policymakers should encourage financial institutions to provide more significant opportunities for companies that audit financial statements to access larger amounts of capital and faster disbursement of funds. Firms should provide greater opportunities for women to occupy positions as top managers. It is the company's responsibility to promote gender sharing programs, particularly for the human resources department. Our study integrates the concepts of financial statement audits, access to finance, and the gender of firm managers into a model to predict how firms comply with their tax obligations.
Keywords: 330; access to finance; financial statement audits; gender top manager gender; tax compliance